Ceramic buckling for determining the residual stress in thin films. (August 2021) - Gao, Zhaohe; Zhang, Xun; Kulczyk-Malecka, Justyna; Chen, Ying; Bousser, Etienne; Kelly, Peter; Xiao, Ping
Abstract: A new technique for determination of residual stress in thin films and coatings has been presented. The method consists of focused ion beam milling to create a lamella of thin film, followed by analysis of stress driven buckling profile of undercut lamella (beam) to extract residual stress. The residual stresses in crystalline TiN and Al2 O3 films, produced by reactive magnetron sputtering and thermal oxidation, respectively, have been successfully determined by this new technique and validated by conventional X-ray diffraction and photoluminescence piezospectroscopy techniques, respectively. This new technique successfully measures and tracks the evolution of residual stress in as-deposited and different thermally cycled amorphous SiAlN films induced by thermal mismatch or relieved via mechanical twinning in interlayer, where diffraction methods are not applicable, thereby evaluating the thermal cycling performance of amorphous SiAlN coatings for protection of Ti at high temperature. Graphical abstract: Image, graphical abstract